Combination of Wells clinical score and high D-dimer levels in the diagnosis of pulmonary embolism. Issue 4 (2014) - Yılmaz, Süreyya; Topçu, Füsun; Şen, Hadice Selimoğlu; Abakay, Özlem; Yılmaz, Zülfükar
No abstract available